Tectonoestratigrafia da faixa Brasília Meridional e estudo de casos de possíveis rochas fonte de diamante, Coromandel-MG - Augusto Fonseca Fernandes (2013)
The Coromandel region in West Minas Gerais is geologically located in the Southern part of the Brasília Belt at the Alto Paranaíba Arch. The area has been mapped in a scale of 1:50.000, and subdivided, from W to E, into tectonostratigraphic terrenes called Araxá, Rio Verde, Chapada dos Pilões, Vazante and St. Antônio do Bonito. They are overllaped (respectively) by thrust faults that correspond to the Araxá, Ibiá, Canastra and Vazante Grs. Overlying the sequence occur, in angular unconformity, rocks of the Mata da Corda Gr., divided into the Patos (kimberlite, kamafugites and related rocks) and the Capacete (pyroclastics and epiclastics) Fms. The Araxá Gr. is composed of a metaígneous unit (amphibolites, granites, iron quartzites and graphitic phyllites) and a metasedimentary unit (schists, phyllites, and quartzites). The Ibiá Gr. is represented by rhythmic phyllites of the Rio Verde Fm. and the Canastra Gr. by quartzites, schists and phillites of the Chapada dos Pilões Fm. The Vazante Gr. was divided into the Lagamar and Serra do Garrote Fms, composed of pelitic and dolomitic rocks and the St. Antônio do Bonito Fm. represented by diamictites, pellites and conglomeratic quartzites. The sheets were compartmented in two structural domains: an Internal (Araxá, Ibiá and Canastra Grs) and an External (Vazante Gr.). Both domains have been affected by a single progressive deformation event, which began in a ductile environment and terminated at brittle-ductile conditions. In the Internal Domain the main foliation (Si2//Si1//S0) shows N-S trend, dipping mostly to the W, while at the External Domain the main foliation (Se1//S0) presents a NE-SW trend, dipping towards NW. During a later deformational phase kilometric scale folds have been formed generating thrust faults. During this phase the Coromandel Anticline was developed, which configures a nappe that overlaps the units of the Internal Domain as sets of an imbricate thrust system. A precursor basin model is described, where the rocks of the Vazante Gr. (Lagamar. and Serra do Garrote Fms.), and the Canastra and Araxá Grs. have been deposited in a Passive Margin (1.1-1.0 Ga). The St. Antônio do Bonito Fm. (of the Vazante Gr.) was deposited during a later glacial event (1.0-0.9 Ga). The last to be formed was the Ibiá Gr., already during the collisional phase, when at the same time the intrusion of the syn-collisional granites from the Araxá Gr. occured. Cases Studies concenrning diamond occurrences have been carried out at Canastrel and Wilson garimpos and at Douradinho 10 and França 1 kimberlite bodies. In all the cases kimberlite indicator minerals show the same compositional trend. The Garimpo Canastrel is located in the rocks of the Capacete Formation, composed of conglomerates, pyroclastic rocks, arenites and tuffs, derived from volcanic bodies of the Alto Paranaíba Arch. Three diamonds have been recovered from conglomeratic rocks at the Garimpo Canastrel. The Garimpo Wilson occurs at a paleo alluvium of the St. Antônio do Bonito River, which is composed exclusively of Capacete Fm. and Canastra Gr. rocks. Mapping suggests that the basal conglomerates of the Capacete Formation could be the main source rock of diamonds in the Coromandel area.